Control of ventricular unloading using an electrocardiogram‐synchronized pulsatile ventricular assist device under high stroke ratios. Issue 10 (15th May 2020) - Magkoutas, Konstantinos; Rebholz, Mathias; Sündermann, Simon; Alogna, Alessio; Faragli, Alessandro; Falk, Volkmar; Meboldt, Mirko; Schmid Daners, Marianne
Abstract: Pulsatile ventricular assist devices (pVADs) yield a blood flow that imitates the pulsatile flow of the heart and, therefore, could diminish the adverse events related to the continuous flow provided by the ventricular assist devices that are commonly used. However, their intrinsic characteristics of larger size and higher weight set a burden to their implantation, that along with the frequent mechanical failures and thrombosis events, reduce the usage of pVADs in the clinical environment. In this study, we investigated the possibility to reduce the pump size by using high pump stroke ratios while maintaining the ability to control the hemodynamics of the cardiovascular system (CVS). In vitro and in vivo experiments were conducted with a custom pVAD implemented on a hybrid mock circulation system and in five sheep, respectively. The actuation of the pVAD was synchronized with the heartbeat. Variations of the pump stroke ratio, time delay between the pump stroke and the heart stroke, as well as duration of the pump systole in respect to the total cardiac cycle duration were used to evaluate the effects of various pump settings on the hemodynamics of the CVS. The results suggest that by varying the operating settings of the pVAD, a pulsatile flow that provides physiological hemodynamic parameters, as well as a control over the hemodynamic parameters, can be achieved. Additionally, by employing high pump stroke ratios, the size of the pVAD can be significantly reduced; however, at those high pump stroke ratios, the effect of the other pump parameters diminishes.